The transformation pathways and optimization of conditions for preparation minor ginsenosides from Panax notoginseng root by the fungus Aspergillus tubingensis - Fei-Xing Li; Dong-Mei Lin; Jin Yang; Xiu-Ming Cui; Xiao-Yan Yang (PLoS ONE, 2025)
Minor ginsenosides exhibit enhanced pharmacological effects in comparison to the major ginsenosides. However, the natural content of minor ginsenosides in plants is typically insufficient to satisfy clinical demand. Therefore, we investigated the biotransformation of the major ginsenosides in Panax notoginseng to minor ginsenosides by the fungus Aspergillus tubingensis. The transformation products were analyzed using TLC, HPLC, and LC-MS techniques to propose the biotransformation pathways of major ginsenosides. A. tubingensis was found to transform the main ginsenosides into 15 minor ginsenosides, inculding (R/S)-Rg3, Rk1, Rg5, F2, (R/S)-Rh1, Rk3, Rh4, (R/S)-Rg2, F4, Rg6 and (R/S)-R2. The transformation reactions encompassed isomerization, hydrolysis and dehydration. We have also optimized the reaction temperature and pH for the crude enzyme extracted from this fungus, which has a molecular weight of 66 kDa. Based on our current knowledge, this transformative characteristic of A. tubingensis was initially documented for the concurrent transformation of PPD and PPT type saponins in P. notoginseng. This method of preparing minor saponins will be valuable for the development of P. notoginseng as a traditional medicinal material.